2010
DOI: 10.1193/1.3460374
|View full text |Cite
|
Sign up to set email alerts
|

A Ground Motion Scaling Method considering Higher-Mode Effects and Structural Characteristics

Abstract: As nonlinear response history analysis (NLRHA) becomes a frequently used procedure for the seismic demand evaluation of multistory buildings, it becomes increasingly important to develop a ground motion scaling method which properly includes the dominating modes in the seismic demand estimates. This paper proposes a multimode ground motion scaling (MMS) method, which applies the square root of the sum of the squares (SRSS) or complete quadratic combination (CQC) rule in computing peak seismic demands. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…However, these IMs do not account for higher vibration modes of the structure and non-linear effects, such as elongation of natural period [5,[13][14][15][16][17]. To address this concern, several contemporary IMs have been proposed to accommodate the characteristics of both the ground motion and the structure [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Ground Motion Intensity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these IMs do not account for higher vibration modes of the structure and non-linear effects, such as elongation of natural period [5,[13][14][15][16][17]. To address this concern, several contemporary IMs have been proposed to accommodate the characteristics of both the ground motion and the structure [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Ground Motion Intensity Measuresmentioning
confidence: 99%
“…Housner [46] defined actual damage to structures as the difference between relative input energy and damping energy. Equations (18) and (19) are equivalent velocities that represent the relative input energy and damage energy, respectively.…”
Section: Energy Imsmentioning
confidence: 99%
“…Twenty Los Angeles 10% in 50-year seismic hazard level ground motions developed for the SAC joint research project (Gupta and Krawinkler 1999) were used in this study. The earthquake ground accelerations were all scaled (Weng et al 2010) to the Sa = 1.07 g in the DBE response spectrum at the fundamental period of T = 0.429 s as shown in Figure 7b. The OpenSees nonlinear dynamic analysis results showed that the LA03 acceleration record scaled to the PGA = 597 cm/s 2 are within the limit of the NCREE laboratory's facility.…”
Section: Hybrid Tests and Analytical Studies Of The Three-story Scbf Specimenmentioning
confidence: 99%
“…Wang concluded that GMs selected based on this procedure exhibited better efficiency and sufficiency in capturing the seismic responses. Weng et al 22 proposed a GM selection and scaling method incorporating the dominant modes of vibration. Bradley et al 23 evaluated various methods of GM simulations as alternatives to empirical Ground Motion Prediction Equations (GMPEs) to generate a set of hazard‐consistent synthetic records.…”
Section: Introductionmentioning
confidence: 99%